1976
DOI: 10.1085/jgp.67.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport studies and determination of the cell wall elastic modulus in the marine alga Halicystis parvula.

Abstract: A ~ S x 1~ A C X Using cultured cells of the marine alga, Halicystis parvula, we measured the concentrations of 11 inorganic ions in the vacuolar sap and the electrical potential difference (PD) between the vacuole and the external solution. In normal cells under steady-state conditions a comparison of the electrochemical equilibrium (Nernst) potential for each ion with the PD of -8~ mV (inside negative) indicates that Na + and K + are actively transported out of the vacuole whereas all anions are pumped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…The Valonia plasmalemma potential of about -70 mv found here is of similar magnitude to the value in other marine algae (12,15), with the exceptions of Nitellopsis obtusa, where it is -130 mv (21), and Acetabularia mediterranea, where it is -170 mv (26). The values of E,, in freshwater algae and in higher plants are usually somewhat higher than in Valonia and range from about -I10 to about -200 mv (18).…”
Section: Effects Of Concentration Changes Of Other Ions In Aswsupporting
confidence: 78%
“…The Valonia plasmalemma potential of about -70 mv found here is of similar magnitude to the value in other marine algae (12,15), with the exceptions of Nitellopsis obtusa, where it is -130 mv (21), and Acetabularia mediterranea, where it is -170 mv (26). The values of E,, in freshwater algae and in higher plants are usually somewhat higher than in Valonia and range from about -I10 to about -200 mv (18).…”
Section: Effects Of Concentration Changes Of Other Ions In Aswsupporting
confidence: 78%
“…Cl ) also plays a major role in Derbesia. Active Cl ) transport carries 90% of the short circuit current, and short circuit current varies with turgor (Graves & Gutknecht, 1976).…”
Section: Other Marine Chlorophytesmentioning
confidence: 99%
“…Kamiya et al (17) showed that when pressure in a cell wall tube of Nitellaflexilis was increased in steps and then decreased with the same steps, the volume changes of the wall ' The values of e found for plants range over 3 orders of magnitude (25). For the giant-celled algae maximum values of e range from 0.06 MPa for Halicystis parvula (13) to 70 MPa for Chara corrallina (10). Maximum values of e so far found for higher plants are generally lower than those for the algae and range from 0.19 MPA for A Ilium cepa bulb epidermis cells (11) to 30 MPa for Pernettya macronata (9).…”
mentioning
confidence: 99%